CROATIAN STUDENTS AND ALCOHOL CONSUMPTION – IMPLICATIONS FOR SOCIAL MARKETING - Sofija Turjak; Mirna Leko Šimić (Ekonomska Misao i Praksa, 2018)
Social marketing as a discipline that promotes products, services and ideas for voluntary behaviour change can be implemented in solving alcohol abuse problems. The WHO report (2014) on global alcohol abuse positioned Croatia on a high fourth place with an average of 15.1 litres of annual alcohol consumption per capita. To develop efficient marketing programmes for change of youth alcohol abuse, it is necessary to analyze existing behaviour, motivations and attitudes toward alcohol consumption, which is the aim of this paper. A sample of 379 students of a university from Croatia participated in the research. For the purposes of this study three measurement instruments were used: the AUDIT (Alcohol Use Disorder Identification test), motivation measurement for alcohol consumption and demographic questionnaire. The majority of respondents (54%) belong to the group of moderate alcohol consumers. The most important alcohol consumption motives for Croatian students belong to the group of social motives, i.e. to obtain positive social rewards. In general, the most consumed types of alcoholic drinks at home are wine and beer/cider, but at bars or in clubs where most of alcohol is actually consumed in case of students, there is strong preference for spirits. Majority of respondents consume alcohol during weekend nights. The major target group to aim social marketing efforts at are male students at undergraduate level, aged 23 or less that live either with their parents or with fellow students in private accommodation (out of campus). The major marketing efforts should be directed toward promotion of different, alcohol-free, or responsible drinking lifestyles.